ANALISIS EFEKTIVITAS BIAYA PENGGUNAAN ANTIBIOTIK SEFTRIAKSON DAN SEFTAZIDIM PADA PASIEN PNEUMONIA DEWASA DI RAWAT INAP RSUD AJIBARANG PERIODE JANUARI – DESEMBER 2021 - Adi Susanto; Eko Hidayaturohman Khumaeni; Lina Septiana (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2022)
Pneumonia is a world health problem with the highest mortality rate, both in developed and developing countries such as Indonesia. Pneumonia is an acute infectious disease that affects the lung parenchyma (alveoli) so that the lung tissue becomes inflamed. To treat pneumonia, appropriate antibiotics are needed, minimal side effects and affordable costs. So it is necessary to study the cost-effectiveness analysis in order to make it easier to choose a more cost-effective treatment in pneumonia patients. The purpose of this study was to determine the cost-effectiveness of the use of antibiotics ceftriaxone and ceftazidime in adult pneumonia patients in Ajibarang Hospital inpatient period January – December 2021. This study was a descriptive study with retrospective data collection. Sampling using total sampling method and data collection using patient medical records. The results showed that the ACER value of the antibiotic ceftriaxone was Rp. 17,468 with an effectiveness of 87%, while the ACER value of ceftazidim is Rp. 15,375 with 100% effectiveness. In the quadrant placement the cost-effectiveness of ceftazidime occupies the dominant column in quadrant II (higher effectiveness with lower cost). Based on the ACER value and cost-effectiveness quadrant, ceftazidime is a more cost-effective therapy than ceftriaxone because it has a lower ACER value and occupies the dominant column.